EMPLOYEE TURNOVER INTENTION - Nur Faliza; Fakrurrazi; Ibrahim Qamarius (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
For company, turnover is an important factor that needs to be considered, because it relates to the behavior of its employees who have the intention to leave so that it greatly impacts company outcomes. This study aims to examine the effect of job satisfaction, career development and organizational commitment on employee turnover intention. The method used in this study is multiple linear regression analysis. The results of the analysis show that job satisfaction, career development and organizational commitment have an effect on employee turnover intention.